The Scope and Selectivity of Comparative Area Studies: Transitional Justice Research - Anika Oettler (German Institute of Global and Area Studies (GIGA), 2014)
The paper discusses how current methodological debates on the potential of comparative area studies intersect with current trends in transitional justice research. As the field of transitional justice studies is approaching saturation, academic efforts in this field are increasingly focused on empirical as well as theoretical generalization. The challenge of comparative transitional justice research is less to weigh the national impacts of policies than to incorporate a more historicized conception of causality that includes complex longterm processes and global interdependencies. From the perspective of comparative area studies, the case of transitional justice studies testifies to the need to combine the local, national, transnational, translocal, and global levels of analysis.
Keywords: 300; area studies; comparative area studies; transitional justice; comparison